DEGRADATION KINETICS OF ANTHOCYANINS DURING HEAT TREATMENT OF WILD BLACKTHORN (Prunus spinosa L.) FRUITS EXTRACT - MOLDOVAN, Bianca; ARDELEAN, Anamaria; DAVID, Luminiţa (Studia Universitatis Babeș-Bolyai Chemia, 2019)
The blackthorn (Prunus spinosa L.) fruits are known as a valuable source of anthocyanins and for their high antioxidant capacity. The aim of the present study was to investigate the thermal stability of anthocyanins from blackthorn fruits, at different temperatures (2°C, 20°C and 75°C) and to determine the kinetic and thermodynamic parameters of their degradation reactions. Data analysis indicated a first-order reaction kinetics for the degradation of blackthorn anthocyanins at various temperatures. Kinetic parameters, such as reaction rate constant k, half-life t1/2, and activation energy Ea values were determined. The obtained results indicated that blackthorn anthocyanins stored at 2°C exhibited the highest stability, the degradation constant rate being 5.0·10-4 h-1. The activation energy of the thermal degradation was also determined and was found to be 53.96 kJ/mol. The activation enthalpy ΔH¹, Gibbs free energy ΔG¹ and activation entropy ΔS¹ for the degradation process were also determined.